Effect of Self-Management Program on Health Related Quality of Life in Patients with Diabetic Retinopathy - Phansathian, Nitchchanun; Navicharern, Rungrawee (Srinagarind Medical Journal, 2024)
Background and Objective: Diabetic retinopathy can lead to ocular disturbances and loss of vision. The evidence showed that self-management program could increase quality of life in patients with diabetic retinopathy. This study aimed to investigate the effect of self-management program on health-related quality of life in patients with diabetic retinopathy. Materials and Methods: Quasi-experimental research with two group pretest-posttest design. The subjects were type2 diabetes’s adult between 18-59 years old patients with diabetic retinopathy in the Eye clinic at Out patients department, Srinagarind Hospital. The 72 samples with purposive sampling were equally divided into control and experimental group of 36 persons each. The control group received routine nursing care only, but the experimental group received the self-management program. The self-management program was based on Lorig and Holman’s concept of self-management combined with Diabetes Self-Management Education. The duration time of the program was conducted over a period of 12 weeks. The instrumentation for collecting data were a demographic data form and Thai Visual Function Questionnaire. The instrumentation was tested for reliability with Cronbrach’s alpha coefficient at .82. The data were analyzed by using frequency, percentage, mean, and standard deviation. The hypotheses were test using paired sample t- test and independent sample t –test Result: The mean score level of health-related quality of life after experiment of experimental group were statistically significant higher (84.61±6.22) than before experiment (82.19±9.42) (t-test = 2.61) and also higher than control group (73.99±12.56) (t-test = 4.55) at the level of p< .05 Conclusion: The self-management program could increase health-related quality of life in patients with diabetic retinopathy.